Autonomic nervous system activity and dialectical behavioral therapy outcome in adolescent borderline personality pathology. (9th August 2021) - Weise, Sindy; Parzer, Peter; Fürer, Lukas; Zimmermann, Ronan; Schmeck, Klaus; Resch, Franz; Kaess, Michael; Koenig, Julian
Abstract: Objectives: We aimed to investigate whether pre-treatment cardiac autonomic nervous system (ANS) activity, indexed by heart rate (HR) and heart rate variability (HRV) predicts clinical outcome and therapy drop-outs in adolescents with borderline personality (BPD) pathology receiving dialectical behavioural therapy (DBT-A). We further tested for an association between changes in ANS function and clinical outcome over time. Traumatic experiences were considered as potential confounding factor. Methods: N = 43 (95.4% female, Mage = 15.5 years) adolescents fulfilling at least sub-threshold criteria for BPD (≥3) were investigated before and after outpatient DBT-A as well as at follow-up. N = 10 patients dropped out of treatment (<50% of treatment sessions). Latent growth curve models were used for analyses. Results: Greater pre-treatment resting HRV significantly predicted clinical improvement (decrease in BPD pathology/increase of global functioning) over time. Pre-treatment ANS activity was unrelated to treatment drop-out. Further, changes in ANS activity over treatment were associated with changes in clinical outcome. Conclusion: This study is the first providing evidence that pre-treatment HRV predicts and is related to treatment response in adolescent borderline personality pathology. Implications for the use of ANS measures in clinical practice and directions for future research are discussed.